Rehabilitation of Corruption Convicts: A Modern Sentencing Theory Perspective - Gunawan, Ghani Fauzan; Abdulgani, Rika Kurniasari (jurnal.unprimdn.ac.id, 2026)
This study examines the application of rehabilitation for individuals convicted of corruption offenses through the lens of modern sentencing theory, and proposes normative criteria for its implementation within Indonesian positive law. Using a normative juridical method with statutory, conceptual, and case-based approaches, legal materials were analyzed qualitatively. The findings reveal that rehabilitation in Indonesian law rests on a strong constitutional foundation as an attributed power of the President, and has progressively evolved into an instrument for protecting individual rights within the criminal justice system. However, the existing legal framework remains incomplete, as it does not explicitly accommodate rehabilitation for convicts whose sentences carry permanent legal force—particularly in corruption cases that intersect with business decision-making. From a modern sentencing theory perspective, rehabilitation functions as a corrective mechanism to shield individuals from potential state error, provided it does not compromise the public interest in eradicating corruption. Accordingly, five strict normative criteria are proposed for its application: (1) demonstrable error in the criminal conviction, (2) a lawful basis of authority, (3) relevance to the business judgment rule, (4) adherence to the principle of proportionality, and (5) assurance that no impunity is created. Rehabilitation, under these conditions, should be viewed not as a weakening of criminal law, but as an integral corrective mechanism within the rule of law that sustains a balance among legal certainty, justice, and social utility.